Emotionally Focused Couples Therapy_x000D_ and Spirituality - (:unkn) unknown (My University, 2020)
Emotionally focused therapy was created as a couples therapy approach and has become a frequentlyused therapeutic approach these days. This approach, theoretically based on the understanding thatthe attachment relationship observed between mother and child characterized by proximity seekingand separation anxiety resembles the relationship observed between couples, aims to turn unhealthyattachment relationships between couples into healthy ones. This process is realized by revealing theimplicit and hidden emotions that cause problem situations to occur and gaining awareness aboutthese emotions. Different studies have shown spirituality to be a major factor both in forming andsolving problem situations in therapy for couples who care about spiritual values. In particular, themeanings couples who attach importance to religious values attribute to marriage and the qualityof the relations developed within this meaning can be handled within the framework of emotionallyfocused couples therapy. The purpose of this article is to explain how the therapy process proceedswhen emotionally focused couples therapy is combined with spiritual values and to show whichmethods and techniques are used in the light of sample cases. In addition, the article aims to raiseawareness on how to use this therapy approach, as it can be combined with Islamic elements, andinvestigates how to set an example in this regard. This study, which briefly introduces emotionallyfocused couples therapy, provides short examples of how to perform interventions while working withcouples who seek counseling using religious or spiritual matters

Duygu Odaklı Terapi bir çift terapisi yaklaşımı olarak oluşturulmuş ve günümüzde sıkça_x000D_ kullanılan bir terapi yaklaşımı olmuştur. Anne ve bebek arasındaki bağlanma ilişkilerinde_x000D_ görülen yakınlık ve huzur arayışı ile ayrılma endişesi süreçlerinin bir benzerinin romantik_x000D_ çift ilişkilerinde de görüldüğü anlayışıyla teorik açıdan temellendirilen bu yaklaşımda amaç,_x000D_ çiftler arasındaki sağlıksız bağlanma ilişkilerini sağlıklı hale çevirebilmektir. Bu süreç problem_x000D_ durumlarının oluşmasına sebep olan örtük ve saklı duyguların ortaya çıkarılıp bu duygulara_x000D_ ilişkin farkındalıkların kazandırılmasıyla gerçekleşmektedir. Manevi değerlere önem veren çiftler_x000D_ ile yapılan terapide, hem problem durumunun oluşumunda hem de çözümünde maneviyatın_x000D_ büyük bir etken olduğu yapılan farklı çalışmalarda görülmektedir. Özellikle dini değerlere önem_x000D_ veren çiftlerin evliliklerine atfettikleri anlam ve bu anlam çerçevesinde gelişen ilişkilerin niteliği_x000D_ Duygu Odaklı Terapi yaklaşımı çerçevesinde ele alınabilmektedir. Bu makalede amaç, Duygu_x000D_ Odaklı Terapi yaklaşımının manevi değerler ile birleştiğinde terapi sürecinin nasıl ilerlediği ile_x000D_ ilgili açıklamalarda bulunmak ve terapi yaklaşımının hangi yöntem ve tekniklerinin daha çok_x000D_ kullanıldığını örnek vak’alar eşliğinde göstermektir. Ayrıca İslami ögeler ile birleştirilebilecek_x000D_ bu terapi yaklaşımının nasıl kullanılabileceği konusunda bir farkındalık oluşturularak bu_x000D_ açıdan örnek teşkil etmesi istenmiştir. Bu çalışmada öncelikle Duygu Odaklı Çift Terapisi kısaca_x000D_ tanıtılmış ve daha sonra dinsel veya manevi ögelerle danışmaya gelen çiftlerle çalışılırken müdahale_x000D_ yöntemlerinin nasıl olacağı ile ilgili kısa vak’a örneklerine yer verilmiştir.
Duygu Odaklı Çift Terapisi ve Maneviyat